A multicenter, open-label, long-term study of three-year infliximab administration in Japanese patients with ankylosing spondylitis. Issue 1 (2nd January 2017) - Kobayashi, Shigeto; Yoshinari, Toru
Abstract: Objective : To investigate the efficacy, safety, and pharmacokinetics of infliximab (IFX) in Japanese patients with active ankylosing spondylitis (AS). Methods : In this multicenter open-label study, IFX was infused at 5 mg/kg to 33 Japanese patients with active AS using or intolerable to non-steroidal anti-inflammatory drugs (NSAIDs) at Weeks 0, 2, and 6, and then every six weeks for approximately three years (mean: 149.5 weeks). Results : Assessment in Ankylosing Spondylitis (ASAS) 20 response at Week 24 (primary endpoint) was 97.0% (32/33) and was thereafter maintained at approximately 90% over the three-year study period. Improvements in range of motion, physical function, inflammatory parameters, and quality of life (QOL) were all maintained throughout the three-year study period. A serum IFX level of ≥5 μg/mL was maintained with six-week infusion intervals, and only two patients (6.1%) developed antibodies to IFX. Specific adverse events in AS patients were not observed. Conclusion : These findings suggest that a 5 mg/kg administration of IFX at six-week intervals to Japanese patients with active AS is safe, effective and provides long-term therapeutic benefits.